İYONKÜREDEKİ TERMOKÜRESEL RÜZGARLAR - AKSAKAL, HÜSNÜ (Fırat Üniveristesi, 2000)
Bu çalışmada, iyonküredeki termoküresel (nötr) rüzgarlar (40° K, 40° D) coğrafik koordinatı için F2-bölgesinin tepe yüksekliği (hmF2)'de incelenmiştir. Nötr havanın hareket denklemi çözülerek, nötr rüzgarın kuzey-güney (Uy) ve doğu-batı (Ux) bileşenlerinin matematiksel ifadeleri elde edildi. Bu ifadeler kullanılarak nötr rüzgarın Uy ve Ux bileşenlerinin nümerik değerleri hesaplandı. Hesaplamalar için gerekli olan parametreler International Reference Ionosphere (IRI) modelinden elde edildi. Nötr rüzgar hızının günlük ve mevsimsel değişimleri incelendi. 21 Aralık'ta nötr rüzgarın hızı maksimumdur (~200 m/s). Uy hızı yaklaşık olarak saat 06-18 yerel zaman (YZ) arasında kutuba, günün geri kalan saatlerinde ise ekvatora doğrudur. Ux hızı ise yaklaşık 02-14 YZ arasında batıya doğru iken, günün diğer saatlerinde doğuya doğrudur. Ayrıca nötr rüzgarın düşey bileşeni hesaplanarak bu hızın iyonküre plazması üzerindeki etkisi araştırıldı. Düşey hızın yönü gündüz saatlerinde aşağıya, gece saatlerinde ise yukarıya doğrudur. Bu hız gündüz saatlerinde hmF2 tepesini aşağıya, gece saatlerinde ise yukarıya doğru hareket ettirir. Nötr rüzgar gündüz saatlerinde elektron yoğunluğunu azaltır gece saatlerinde ise artırır Son olarak, IRI modeli kullanılarak hesaplanan Ux ve Uy hızlan, Horizontal Wind Model (HWM-93) ile elde edilen Ux ve Uy hızlan karşılaştırıldı. Anahtar Kelimeler : İyonküre, termoküre, nötr rüzgarlar, düşey hız.

In this study, thermospheric (neutral) winds in the ionosphere have been investigated for geographic coordinates of (40° K, 40° D) at F2 peak height (hmF2). The mathematical expressions of north-south (Uy) and east-west (Ux) components of the neutral wind have been obtained by solving the equation of neutral air motion. The numerical values of Uy and Ux have been calculated by using this expression. The ionospheric parameters which are necessary for the calculations are obtained from International Reference Ionosphere Model-95 (IRI95). The diurnal and seasonal variation of neutral wind velocity has been investigated. The neutral wind velocity is maximum (~200 m/s) at 21 December. Uy velocity is poleward approximately between 06-18 LT and it is equatorward during the rest hours of the day. Ux is westward between 02-14 LT and it is eastward during the rest hours of the day. In addition, the effect of this velocity on ionospheric plasma has also been examined by computing the vertical component of neutral wind. The vertical velocity is downward during the daytime and upward during the nighttime. During the daytime this velocity moves the hmF2 height downward and upward during the nighttime. The neutral wind decrees the electron density during the daytime and increases during the nighttime. Finally the calculated of the Ux and Uy velocities using IRI-model, were compared with the Ux and Uy velocities obtained by Horizontal Wind Model (HWM- 93) Key Words: Ionosphere, thermosphere, neutral winds, vertical velocity.
Thermospheric winds in the ionosphere
Keywords: Fizik ve Fizik Mühendisliği; Physics and Physics Engineering